Strategi Komunikasi Pengelolaan Website tribratanews.sumsel.polri.go.id dalam Meningkatkan Branding Polda Sumatera Selatan - Okta Monica Putri; Selvia Assoburu; Sri Hertimi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Tribunnews states that the Indonesian National Police ranks lowest in terms of public trust compared to other institutions such as the Attorney General's Office, the courts, and the Corruption Eradication Commission. The police force uses its official website to improve its branding. Although websites are a very fast tool for disseminating information compared to other mass media, it is very difficult to attract visitors to websites. This study aims to identify the various communication strategies used by the South Sumatra Regional Police in managing the tribratanews.sumsel.polri.go.id website and how the website operates to enhance the branding of the South Sumatra Regional Police. This study uses a descriptive qualitative method in the form of interviews, documentation, and observation, and the results are presented in a descriptive manner. The results show that the communication strategy used by the South Sumatra Regional Police in managing the tribratanews.sumsel.polri.go.id website is to apply the Agenda Setting theory and use the PII (Preparation, Implementation, and Impact) Analysis model. Additionally, it was found that the role of the tribratanews.sumsel.polri.go.id website is to serve as a platform for publishing all police activities in South Sumatra, enhancing public understanding, and shaping a more positive perception of the police institution as a transparent, professional, and humane organization.